Bacteriocin Produced by Lactobacillus acidophilus Exhibits Antagonistic Activity Against Uropathogenic Klebsiella pneumoniae - Jenan Atiyah Ghafil; Zainab Hani Hatif (World Journal of Experimental Biosciences, 2025)
Antibiotic resistance in bacteria is a major problem facing the health system worldwide. The ability of bacteria to form biofilms enhances their resistance to antibiotics. Finding alternative antimicrobial agents is a crucial approach in the global fight against infectious diseases caused by multidrug-resistant bacteria. In this study, yogurt samples were cultured on Man–Rogosa–Sharpe agar (MRS) to isolate Lactobacillus acidophilus. Fifty urine samples were collected from patients with urinary tract infections (UTI). Eleven isolates of Klebsiella pneumoniae were obtained from these samples. The bacteriocin was extracted from L. acidophilus grown in MRS broth. Ammonium sulfate at 70% saturation was used for the partial purification of the bacteriocin. The gel diffusion method evaluated the antibacterial effect of both crude and partially purified bacteriocin on MDR-K. pneumoniae, which produced the highest level of biofilm. The ability of the 11 isolates of K. pneumoniae to produce biofilm was assessed using the microdilution method in a polystyrene microtiter plate. The results showed that out of eleven isolates, eight were MDR. All isolates produced biofilm at different levels. Both crude and partially purified bacteriocin (at dilutions 1/2, 1/4, 1/8, 1/16, and 1/32) inhibited the growth of Kp9. The partially purified bacteriocin was more effective than the crude form in inhibiting Kp9 growth. Sub-MICs (1/2, 1/4, 1/8, and 1/16 MICs) of both crude and partially purified bacteriocin inhibited biofilm formation of Kp9. The bacteriocin from L. acidophilus has the ability to inhibit MDR-K. pneumoniae and its capacity to prevent biofilm formation in vitro.
Keywords: Antibiofilm, Antagonism, Bacteriocin, Klebsiella pneumoniae, UTI.